EFEKTIFITAS PROGRAM CSR (CORPORATE SOCIAL RESPONSIBILITY) PADA YAYASAN GADA ULIN BATULICIN - , Edy Rusdi ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Mine exploitation conducted in South Kalimantan particularlyin the District of Tanah Bumbu seasonings has been going on a large scale since 2003. Theseactivities brought both positive and negative impacts on the surrounding community. The existence Corporate Social Responsibility is an effort of the company to maintain harmony with people around the mining activities of PT. AI Site Batulicin.The implementation of CSR programs by PT. AI is done by YGU in its efforts to improve the welfare and empower people in 12 villages targeted program.This study aims to describe the process of community empowerment by YGU around the mine area, measuring the effectiveness of the economic program YGU and the factor that affect the sustainability of KSM formed so as to maintain. Descriptive methodconducted qualitatively using deductive approach. The data collection is done by in-depth interviews, based on field observation and assessment documents. In general, the study showed that the productivity of the economic program is a high. On the other hand, the measurement of the effectiveness of the economic program in a KSM was foundvery low (not effective). Butit has improved the welfare of the community. The program is quite effective in preserving the Dana MitraGadaUlin so that it can yield results by Gakin.